The Influence of PBL Based on a Pedagogical Approach on Improving the Critical Thinking Ability of MA NW Lenek Lauk Students - Rizkiwati, Baiq Yuliana; Mispandi, Mispandi; Wardah, Diki Wardiman Saleh (IJE : Interdisciplinary Journal of Education, 2024)
This study aims to find out whether the Problem Based Learning learning model  based on the reflective pedagogy approach has an effect on improving students' critical thinking skills in economic learning in class X students at MA NW Lenek Lauk. This study is a Quasi Experiment research with a control group design  of randong sampling. The research sample is 23 students for the experimental class and 25 students for the control class. The data collection technique uses tests in the form of Pretest and Posttest questions and uses questionnaires or questionnaires. The hypothesis proposed in this study is that there is an influence  of the Problem Based Learning (PBL) learning model based on a reflective pedagogical approach on improving the critical thinking ability of grade X students in the independent curriculum for economics subjects at MA NW Lenek Lauk. Data analysis using an independent t test with a significant value of 5 % (0.05) can be obtained  with a sig.( 2-tailed) by 0.000 < 0.05. It can be concluded that Ha is accepted and Ho is rejected, so  the Problem Based Learning (PBL) Learning Model Based on a Reflective Pedagogy Approach has an effect on improving the critical thinking skills of class X students in the Independent Curriculum for Economics Subjects at MA NW Lenek Lauk.